Sistem Pakar Menggunakan Metode Backward Chaining Untuk Mengantisipasi Permasalahan Tanaman Kacang Kedelai Berbasis Web - Zufria, Ilka; Santoso, Heri; Darsih, D (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
Soybeans (Glycine max (L.) Merill.) are an important source of protein in Indonesia, it is a part of variety of beans. The soybeans’ need is increasing as people demand for raw materials. While there are so many problems with soy plants that they cause the decline in soy production. The decline in the production of soybean plants has been due to both pest and disease factors. Therefore in this condition it would require an expert to address the problem of soy farmers, but in this condition the lack of an expert and the time of the expert is a problem, so with by existence expert system can provide an alternative to addressing problems. This system of experts can be used to help soy farmers in an effort to identify pests and crop diseases and how the prevention and treatment of pest and soy diseases. The system was used Backward Chaining methods. This application made based Web used PHP programming language.